Comprehensive characterization of the human pancreatic proteome for bioengineering applications. (March 2021) - Asthana, Amish; Tamburrini, Riccardo; Chaimov, Deborah; Gazia, Carlo; Walker, Stephen J.; Van Dyke, Mark; Tomei, Alice; Lablanche, Sandrine; Robertson, John; Opara, Emmanuel C.; Soker, Shay; Orlando, Giuseppe
Abstract: Interactions between the pancreatic extracellular matrix (ECM) and islet cells are known to regulate multiple aspects of islet physiology, including survival, proliferation, and glucose-stimulated insulin secretion. Recognizing the essential role of ECM in islet survival and function, various engineering approaches have been developed that aim to utilize ECM-based materials to recreate a native-like microenvironment. However, a major impediment to the success of these approaches has been the lack of a robust and comprehensive characterization of the human pancreatic proteome. Herein, by combining mass spectrometry (MS) and multiplex ELISA, we have provided an improved workflow for the in-depth profiling of the proteome, including minor constituents that are generally underrepresented. Moreover, we have further validated the effectiveness of our detergent-free decellularization protocol in the removal of cellular proteins and retention of the matrisome. It has also been established that the decellularized ECM and its derivatives can provide more tissue-specific cues than traditionally used biological scaffolds and are therefore more physiologically relevant for the development of hydrogels, bioinks and medium additives, in order to create a pancreatic niche. The data generated in this study would contribute significantly to the efforts of comprehensively defining the ECM atlas and also serve as a standard for the human pancreatic proteome to provide further guidance for design and engineering strategies for improved tissue engineering scaffolds. Graphical abstract: Image 1